Inaktivasi Termal Spora Talaromyces Sp. Berumur 60 Hari Dalam Jus Nanas - Fryda Kusumawati Khoirunnisa; Evelyn Evelyn; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Talaromyces sp. is a spore-forming fungi and has been identified as spoilage in fruit-based medium such as pineapple and tomato. The purpose of this study was to determine the effect of temperature on the thermal inactivation of Talaromyces sp. spores of 60 days in pineapple juice and determine D-value and z-value in the process of Talaromyces sp. in pineapple juice. It was shown that higher temperature resulted in the decreasing of time needed to inactivate the spores. The D-value obtained at temperatures of 80, 85, 90 °C were 67.11, 25.33, and 4.80 minutes. The following z-values were also obtained were 8,7 °C for 60 days age. The result of this study indicate the importance of temperature for the heat resistance of two-month old Talaromyces sp. spores in pineapple juice.Keywords: inactivation, pineapple, resistance, spore, talaromyces sp.